Determinan Faktor yang Mempengaruhi UMKM Menggunakan E- Commerce Sebagai Media Pemasaran - Neni Sri Wahyuni; Muhammad Nelson Pinem; Sri Rahayu; Azwansyah Habibie; Suginam Suginam; Anggia Sari Lubis (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Development of technology today makes it easy to access information via the internet. The development of the internet affects the life of people who live side by side with gadgets and the internet. E-commerce is a model in the process of buying and selling products or services through the internet network. Current technological developments open wider market opportunities for MSMEs. The use of technology is a challenge for MSMEs to survive in the current industrial era 4.0. The main function of using technology is to facilitate every transaction made. This study aims to examine and explain the determinant factors (utility, convenience, attitudes, subjective norms, behavioral control) that influence MSMEs to use e-commerce as a marketing medium in Medan City. This research was conducted on MSMEs that are members of the Indonesian Women Entrepreneurs Association (IWAPI) using the through questionnaire method, the researchers obtained 100 respondents. The results obtained using SPSS with the validity test, reliability test, classical assumption test, multiple linear regression, and hypothesis testing can be concluded through the t test that, usefulness variables, attitude variables, subjective norm variables, behavioral control variables do not affect the use of e- commerce for IWAPI-assisted MSME actors, while the convenience variable affects the use of e-commerce for IWAPI-assisted MSME actors.